The Impact of Augmented Reality in Consumer Behaviour - M, Niveditha; Ancy Stepheno, S (Shanlax International Journal of Management, 2024)
Consumer behaviour is being revolutionized across different sectors by Augmented Reality (AR). This paper provides a conceptual study addressing how AR applications affect consumer behaviour across multiple industries. This research, focuses on how augmented reality (AR) in retail uses personalized product information and virtual try-on experiences to help consumers make well-informed decisions. It shows how AR in education fixes subject learning through interactive lessons and real-time information in travel. This research, the study investigates the effects of AR on consumer engagement, brand perception and purchasing behaviour. The objective of this study is to understand how AR influences consumer behaviour, brand loyalty and economic drivers. The methodology involves the review of relevant literature on AR applications, consumer behaviour, and marketing strategies. According to the research, it confirms that AR dramatically enhances customer experience, engagement, and purchase intention. The theoretical foundations that describe how AR enhances the customer experience and drives purchase decisions. The paper also explains the challenges and opportunities presented by the adoption of AR, concluding that AR will change how customers interact and experience the product or store, creating both challenges and opportunities for marketers as they try to adapt to the new reality.